Bio-efficacy and selectivity of different herbicides against weed flora in wheat (Triticum aestivum) - PAL, SURESH; SHARMA, RAJVIR; SHARMA, H B; SINGH, RAGHAVENDRA; BABU, SUBHASH (The Indian Journal of Agricultural Sciences, 2015)
Field experiment was carried out during two consecutive rabi seasons of 2008-09 and 2009-10 at Research Farm of Division of Agronomy, Indian Agricultural Research Institute, New Delhi, to evaluate the bio-efficacy and selectivity of different herbicides against weed flora in wheat (Triticum aestivum L.). Data reveals that readymix applications of mesosulfuron+iodosulfuron (24.0 + 4.8 g/ha) caused the highest reduction in the total weed density and weed dry matter accumulation during both the years at all stages of crop growth which however was statistically at par with mesosulfuron+iodosulfuron (18.0+3.6 g/ha), sulfosulfuron+ metsulfuron (20.0 + 4.0 g/ha), and clodinafop+metsulfuron (60.0 + 4.0 g/ha). With regards to yield attributes and grain yield, application of sulfosulfuron and metsulfuron (20.0+4.0 g/ha) were recorded the maximum values of effective tillers/plant (11.81 and 10.09), length of ear head (10.47 and 9.95 cm), spikelet ear/head (18.29 and 17.89) and number of grains ear/head (53.43 and 53.22) and grain yield (5.57 and 5.17 tonnes/ha) which was closely followed by weed free, mesosulfuron+iodosulfuron (24.0+4.8 g/ ha) and (18.0+3.6 g/ha), tank mix clodinafop+metsulfuron (60.0+4.0 g/ha) during both the years. With respect to economics, highest B:C ratio (1.72 and 1.65) were recorded with the application of sulfosulfuron and metsulfuron (20.0+4.0 g/ha) during both the years.